The Effect of Culture and Competence on Employee Performance Through Job Satisfaction at PT PNM Bangka Belitung Branch - Daniel Silitonga; Siti Safaria (International Journal of Integrative Sciences, 2023)
This study was conducted with the aim of knowing and analyzing the effect of Organizational Culture on Job Satisfaction, the effect of Organizational Culture on Employee Performance, the effect of Job Satisfaction on Employee Performance, the effect of Competence on Job Satisfaction, the effect of Competence on Employee Performance at PT PNM Bangka Belitung Branch.The results showed that Organizational Culture has a positive and significant effect on job satisfaction, Organizational Culture has a positive effect on Employee Performance, Job Satisfaction has a positive and significant effect on performance by, Competence has a positive and significant effect on Job Satisfaction, Competence has a positive and significant effect on Employee Performance